Peranan Analisis Laporan Keuangan dalam Dunia Kerja - Njotoprajitno, Rosemarie Sutjiati (Zenit, 2014)
In Genaral, financial statements are made to record and report all financial data. The financial statements are useful in providing information that can be used by various stakeholders to ensure their interests or needs. Although the financial statements have been proven to deliver tangible benefits, it is still not as much as it should be. In Indonesia, the use of financial statements as resources is limited. Many businesses in Indonesia base their decisions on a variety of other aspectsthat are not well targeted to the root causes of the business. In addition, many investors are unable to understand and utilize the financial statements as a way to ensure the investment success. This article uses a qualitative method to illustrate the benefits of a financial statement analysis and the fact of itsuse in Indonesia. Additionally, it will discuss personal financial statement and analysis and its benefits for individuals. The financial analysis that is easy to understand would be a valuable source of information that can be one of the appropriate bases for decision making and accuracy.Keywords: Financial Statements, Financial Management, Accounting